The Concept of Race and Psychotherapy - Fish, Jefferson M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Is our society color-blind? Trans-racial? Post-racial? And what$1 (Bif anything$1 (Bshould this mean to professionals in clinical practice with diverse clients? The ambitious volume The Concept of Race and Psychotherapy probes these questions, compelling readers to look differently at their clients (and themselves), and offering a practical framework for more effective therapy. By tracing the racial (3z(Bfolk taxonomies(3y (Bof eight cultures in the Americas and the Caribbean, the author elegantly defines race as a fluid construct, dependent on local social, political, and historical context for meaning but meaningless in the face of science. This innovative perspective informs the rest of the book, which addresses commonly held assumptions about problem behavior and the desire to change, and presents a social-science-based therapy model, applicable to a wide range of current approaches, that emphasizes both cultural patterns and client uniqueness. Among the highlights of the coverage: Common elements in therapy and healing across cultures. The psychological appeal of racial concepts despite scientific evidence to the contrary. Lessons psychology can learn from anthropology. Three types of therapeutic relationships, with strategies for working effectively in each. The phenomenon of discontinuous change in brief therapy. Solution-focused therapy from a cross-cultural perspective. Thought-provoking reading for psychologists, psychiatrists, clinical social workers, and other mental health professionals as well as graduate students in these fields, The Concept of Race and Psychotherapy affirms the individuality$1 (Band the interconnectedness$1 (Bof every client.s
Dedication -- Preface -- Acknowledgments -- The Myth of Race -- The Spread of the Race Meme -- How Anthropology Can Help Psychology -- Divided Loyalties and the Responsibility of Social Scientists -- The Conservative-Liberal Alliance against Freedom -- Sociocultural Theory and Therapy -- Common Elements in Therapy and Healing across Cultures -- Discontinuous Change -- Does Problem Behavior Just Happen? -- Prevention, Solution Focused Therapy, and the Illusion of Mental Disorders -- Strategic Thoughts about Solution-Focused Therapy -- A Cross-Cultural View of Solution Focused Therapy -- References -- Credits -- Index.
Keywords: Philosophy (General).; Psychotherapy; Psychology, clinical; Applied psychology; Psychology; Clinical Psychology; Psychotherapy; Cross Cultural Psychology